HUBUNGAN PARITAS, PEKERJAAN DAN DUKUNGAN SUAMI DENGAN TINGKAT KECEMASAN PADA IBU HAMIL DI TEMPAT PRAKTIK MANDIRI BIDAN (TPMB) KEMAYORAN JAKARTA PUSAT TAHUN 2024 - helia Sarahdilla Putri Afriyati; Elli Hidayati (Cahaya Ilmu Bangsa Institute, 2025)
Background: Anxiety in pregnant women is an emotional condition experienced by pregnant women due to a sense of worry and anxiety about their pregnancy. The anxiety rate of pregnant women in Indonesia reaches 373,000,000 and there are 107,000,000 or 28.7% of them experiencing anxiety in facing the labor process which will have an impact on the mother and fetus. Puprposes: This reasearch aims to determine the relationship between parity, employment and husband support with the level of anxiety in pregnant women. Methods: This research used a quantitative observational analytic design method with a cross sectional approach. Data collection techniques using a validated questionnaire. Univariate and bivariate data analysis with Chi-Square test. Results: This research showed that most pregnant women who experienced anxiety were 39 people (52.7%). The number of primigravida pregnant women was 48 people (64.9%), pregnant women who worked were 48 people (64.9%) and pregnant women who received husband support were 49 people (66.2%). The results of data analysis showed there was a relationship between parity (p=0.022), work (p=0.002) and husband support (p=0.004) with the level of anxiety in pregnant women. Conclusion: Parity, occupation and husbands support have a relationship with the level of anxiety in pregnant women at the Independent Midwife Practice Kemayoran, Central Jakarta in 2024.